The Effect of Government Expenditure on Economic Growth in South Sulawesi - Salmawati, Salmawati; Junaidi, Junaidi (LP3M Universitas Putra Bangsa, 2023)
The purpose of this study was to determine the effect of balancing funds on the economic growth of regencies/cities in South Sulawesi Province as measured by the GRDP value. This study specifically analyzes general allocation funds, special allocation funds, and profit-sharing funds, which are considered to have an impact on regional economic growth. The data analysis method used is the Vector Eros Correction Model (VECM) panel, which involves carrying out a stationary test or unit root test, a correlation test, and a Granger causality test. This analysis was carried out with reference to the South Sulawesi Province APBD data for 2019–2021. The results of this study indicate that general allocation funds and special allocation funds do not have a significant effect on economic growth, while profit-sharing funds have a significant effect on the economic growth of districts/cities in South Sulawesi Province.